PROSEDUR AUDIT UTANG USAHA PADA PT. PQR OLEH KANTOR AKUNTAN PUBLIK BHARATA, ARIFIN, MUMAJAD, DAN SAYUTI - Ani Tri Hapsari (2023)
The Public accounting firm Bharata, Arifin, Mumajad, dan Sayuti (KAP BAMS), is an audit service provider that has been registered with the Financial Services Authority (OJK) and has obtained a license to provide audit services from the Ministry of Finance. Audit is an inspection and evaluation activity carried out by the auditor on the financial statements of a company. The audit is carried out with reference to audit procedures, which are a series, flow, or stages to check and test whether or not the presentation of a financial statement is fair. Accounts payable is one of the accounts presented in the financial statements of PT. PQR. This accounts payable arise from credit transactions between the company and other parties whose repayment is borne by the company. PT. PQR in fulfilling its operational activities involves a large amount of accounts payable even within one year there is a significant increase in the balance of accounts payable, so it is necessary to conduct an examination of accounts payable to assess the fairness of their presentation in the financial statements. This report was made to find out the procedures for auditing accounts payable at PT. PQR by KAP BAMS. Based on the implementation of the audit that has been carried out, in the process KAP BAMS has complied with the applicable audit standards in Indonesia.